1994
DOI: 10.1007/bf00408475
|View full text |Cite
|
Sign up to set email alerts
|

Diet, cow's milk protein antibodies and the risk of IDDM in Finnish children

Abstract: Summary Associations of infant feeding patterns and milk consumption with cow's milk protein antibody titres were studied in 697 newly-diagnosed diabetic children, 415 sibling-control children and 86 birth-dateand sex-matched population-based control children in the nationwide "Childhood Diabetes in Finland" study. IgA and IgG antibody titres to the proteins of cow's milk formula, BLG and BSA, and IgM antibody titres to cow's milk formula proteins were measured by ELISA. Several inverse correlations were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 28 publications
2
24
1
4
Order By: Relevance
“…The finding of an independent association of BSA IgG antibody levels with IDDM differs from our earlier results from Finnish and Swedish populations [20,21]. In those studies, the HLA genotype was not included in our multivariate analyses.…”
Section: Discussioncontrasting
confidence: 98%
“…The finding of an independent association of BSA IgG antibody levels with IDDM differs from our earlier results from Finnish and Swedish populations [20,21]. In those studies, the HLA genotype was not included in our multivariate analyses.…”
Section: Discussioncontrasting
confidence: 98%
“…Animal experiments have indicated that development of IDDM can be prevented in diabetes-prone rodents if animals are provided a bovine milk-free diet in early life (Daneman et at., 1987). Shorter duration of breast-feeding and early introduction of dairy products was found to be associated with an increased risk ofIDDM in Finnish and Brazilian children (Virtanen et at., 1991(Virtanen et at., , 1994Oimeno and de Souza, 1997). It has also been reported that patients with IDDM have elevated levels of serum IgO and IgA anti-BSA (bovine serum albumin) antibodies which cross react with p69, one of the target ~-cell antigens in IDDM patients (Karjalainen et at., 1992).…”
Section: Food Plants As Production and Oral Delivery Vehicles For Hummentioning
confidence: 96%
“…Recently, antibodies to various protein constituents present in cow's milk, such as bovine serum albumin, b-lactoglobulin and bovine b-casein and T-cell reactivity to some of the same constituents have been documented in newly-diagnosed IDDM subjects. [9][10][11] Epidemio-logical studies show a strong correlation between the per capita intake of cow's milk and the incidence of IDDM. The incidence of IDDM has also been shown to be inversely related to the duration of breast feeding.…”
Section: Interventionmentioning
confidence: 99%